Exploring the potential of digital storytelling in the teaching of academic writing at a higher education institution in the Western Cape - Mkaza, Linda Olive (university of western cape, 2020)
Magister Educationis - MEd === Writing is an important skill throughout learners’ schooling trajectory because it is through writing that learners need to situate meaning and sense-making across the curriculum. Writing proficiency becomes even more important when learners access tertiary studies. Yet studies suggest that most students struggle with academic writing. Various authors suggest that writing has not been taught appropriately especially in secondary schooling contexts in South Africa and that writing becomes even more daunting for Second Language speakers of English when they reach tertiary education. There is abundant literature on students’ challenges with academic writing and ways to address academic writing challenges but the use of digital storytelling in relation to academic writing development is recent and distinctively underexplored in the literature.